Toward a political philosophy of race - Sheth, Falguni A. 1968- (SUNY series, philosophy and race, 2009)
"Timely, controversial, and incisive, Toward a Political Philosophy of Race looks uncompromisingly at how a liberal society enables racism and other forms of discrimination. Drawing on the examples of the internment of U.S. citizens and residents of Japanese descent, of Muslim men and women in the contemporary United States, and of Asian Indians at the turn of the twentieth century, Falguni A. Sheth argues that racial discrimination and divisions are not accidents in the history of liberal societies. Race, she contends, is a process embedded in a range of legal technologies that produce racialized populations who are divided against other groups. Moving past discussions of racial and social justice as abstract concepts, she reveals the playing out of race, racialization of groups, and legal frameworks within concrete historical frameworks."--Publisher's description.